The TCN2 variant of rs9606756 [Ile23Val] acts as risk loci for obesity‐related traits and mediates by interacting with Apo‐A1. Issue 6 (17th April 2017) - Hebbar, Prashantha; Alkayal, Fadi; Nizam, Rasheeba; Melhem, Motasem; Elkum, Naser; John, Sumi Elsa; Abufarha, Mohamed; Alsmadi, Osama; Thanaraj, Thangavel Alphonse
Abstract : Objective: Despite alarming obesity levels in the Arabian Peninsula, its population lacks convincingly identified genetic determinants of obesity. A genome‐wide association study was performed for obesity‐related anthropometric traits in Arabs and to decipher mechanisms by which the variants mediate traits. Methods: The Illumina HumanOmniExpress BeadChip was used to genotype 1, 353 Arab individuals (largely with Class I obesity) from Kuwait. Genome‐wide association tests for obesity‐related anthropometric traits were performed. Top associations were tested for replication in an independent cohort (1, 176 unrelated Arabs). Resultant variants were investigated for interactions with obesity‐related plasma biomarkers. Pathway analysis was performed on genes harboring markers in linkage disequilibrium (LD) with identified variants. Results: The rs9606756[c.67A>G, p.Ile23Val] variant from TCN2 was associated with waist circumference (WC) at nearly genome‐wide significance ( P  = 8.92E−08). WC was inversely related with Apo‐A1 or high‐density lipoprotein levels; individuals with the AG genotype exhibited stronger relationship than those with the reference AA genotype. Interaction involving the AG genotype (effect allele = G) significantly contributed to an increase in anthropometric traits (particularly WC). Genes harboring single‐nucleotide polymorphisms in LD with rs9606756 mapped onto an interaction network (with TP53 as central element) of established obesity/diabetes‐related protein components. Conclusions: The TCN2 variant acts as a risk factor for WC in the Arab population. The variant mediates obesity‐related anthropometric traits via interactions with Apo‐A1/high‐density lipoprotein or TP53.